USING ENGLISH-LANGUAGE MOVIES FOR EFFECTIVE LANGUAGE LEARNING (International journal of artificial intelligence, 2025)
In today’s globalized world, the English language has become a crucial tool for communication, education, business, and international relations. As a result, learning English has become a priority for students and professionals around the world, including Uzbekistan. Traditional English language instruction often focuses on grammar rules and vocabulary memorization. However, modern teaching methods emphasize the importance of real-life context and immersion. One of the most engaging and effective ways to immerse learners in English is through watching English-language movies. This method not only improves listening and comprehension skills but also provides learners with cultural knowledge, colloquial expressions, and authentic usage of the language. This article explores the role of English-language films in second language acquisition, particularly focusing on their practical and cognitive benefits for learners in non-English-speaking countries.